Digital Customer Experience And Brand Loyalty In The Online Muslim Fashion Industry - Husnah, Nuzul; Sumarto, Siswanda H.; Sjaifudian, Hetifah (Jurnal Ekonomi Syariah Pelita Bangsa, 2026)
This study examines the effect of Digital Customer Experience on Brand Loyalty, with Perceived Value as a mediating variable, in the Online Muslim Fashion industry in West Java, Indonesia. The rapid growth of digital commerce has intensified competition among Online Muslim Fashion brands, making the quality of digital interactions a key factor in shaping customer evaluations and long-term loyalty. This study used a quantitative explanatory design. Data were collected through an online questionnaire distributed to consumers in West Java who had purchased fashion products online at least twice in the last six months and had interacted with a fashion brand through digital platforms. Using purposive sampling, 200 respondents were selected. Data were analyzed using covariance-based Structural Equation Modeling, including Confirmatory Factor Analysis, reliability testing, goodness-of-fit evaluation, structural model testing, and mediation analysis. The results show that Digital Customer Experience positively and significantly affects Perceived Value and Brand Loyalty, while Perceived Value also positively and significantly affects Brand Loyalty. In addition, Perceived Value partially mediates the relationship between Digital Customer Experience and Brand Loyalty. These findings indicate that loyalty in the Online Muslim Fashion industry is shaped by both the quality of digital interactions and the value perceived by consumers.